Distribution of tannin-'tolerant yeasts isolated from Miang, a traditional fermented tea leaf (Camellia sinensis var. assamica) in northern Thailand - Apinun Kanpiengjai (2018)
© 2016 Miang is a fermented food product prepared from the tea leaves of Camellia sinensis var. assamica, and is traditionally produced in mountainous areas of northern Thailand. Although Miang has a long history and reveals deep-rooted cultural involvement with local people in northern Thailand, little is known regarding its microbial diversity. Yeasts were isolated from 47 Miang samples collected from 28 sampling sites, including eight provinces in upper northern Thailand. A hundred and seven yeast isolates were recovered and identified within 14 species based on the comparison of the D1/D2 sequence of the large subunit (LSU) rRNA gene. Candida ethanolica was determined to be the dominant species that was frequently found in Miang together with minor resident yeast species. All yeast isolates demonstrated their tannin-tolerant capability when cultivated on yeast malt agar (YMA) containing 50 g/l tannin, but nine isolates displayed clear zones forming around their colonies, e.g., Debaryomyces hansenii, Cyberlindnera rhodanensis, and Sporidiobolus ruineniae. The results obtained from a visual reading method of tannase revealed that all yeast isolates were positive for methyl gallate, indicating that they possess tannase activity. It is assumed that a tannin-tolerant ability is one of the most important factors for developing a yeast community in Miang. This research study is the first report to describe tannin-tolerant yeasts and yeast communities in traditionally fermented tea leaves.